Ethics and digital media: The pending task of the digital world - Guerrero-Lobo, José Francisco; Villalobos Antúnez, José Vicente; Severino González, Pedro; Prats Palma, Belisario (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
A critique of tension problems between ethics and digital media is elaborated. It focuses on the automation of human referents, subjected to digital control through big data algorithms, accentuating historical data as distinctions that modify reality. This ranges from the robbery of leisure time, to exhausting material resistance, mixing the imperative of innovation, efficiency and excellence in a constant torrent of notifications, reminders and interrelationships. This forges anxieties and wears out of an intense longing, causing a sense of constant accomplishment: being a consultant and entrepreneur is the goal of freedom as self-sacrifice.